2008
DOI: 10.3945/jn.108.094136
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Intestinal Mucosal Phospholipids with Arachidonic and Eicosapentaenoic Acids Fed to Suckling Piglets Is Dose and Time Dependent

Abstract: Infant formula companies began fortifying formulas with long-chain PUFA in 2002, including arachidonic acid (ARA) at approximately 0.5% of total fatty acids. The primary objective of this study was to determine the time-specific effects of feeding formula enriched with supra-physiologic ARA on fatty acid composition of intestinal mucosal phospholipids. One-day-old pigs (n = 96) were fed a milk-based formula for 4, 8, or 16 d. Diets contained either no PUFA (0% ARA, negative control), 0.5% ARA, 2.5% ARA, 5% ARA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…Piglets were randomly allocated to 0, 0.5, 2.5, or 5% ARA or 5% EPA diets differing in fatty acid composition. Dietary fatty acid analysis was previously reported (22). The 18:2(n-6) concentration in the fat blend for the 0%AA diet was 1.5 g/100 g and averaged 20.3 for the other blends (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Piglets were randomly allocated to 0, 0.5, 2.5, or 5% ARA or 5% EPA diets differing in fatty acid composition. Dietary fatty acid analysis was previously reported (22). The 18:2(n-6) concentration in the fat blend for the 0%AA diet was 1.5 g/100 g and averaged 20.3 for the other blends (22).…”
Section: Methodsmentioning
confidence: 99%
“…All procedures were approved by the Institutional Animal Care and Use Committee. Piglets and dietary treatments were the same as described previously (22). Briefly, colostrumfed piglets were acquired at 12-24 h of age and individually caged.…”
Section: Methodsmentioning
confidence: 99%
“…However, growth data for the term infant are less convincing (55). Similarly, growth does not appear to be reduced in young pigs receiving formula supplemented with (n-3) PUFA (56). Relative differences in weights of preterm and term pigs cannot be attributed to differences in overall dietary (n-3) or (n-6) fatty acid concentrations or the (n-6):(n-3) fatty acid ratio, which were similar in preterm and term parenteral solutions.…”
Section: Figurementioning
confidence: 87%
“…These authors also observed that feeding a diet rich in ˆ3 fatty acids lowered the C20:4ˆ6 content of both jejunal and ileal microsomal phospholipids. Last, Hess et al (10) reported that feeding one-day-old pigs a milk-based formula containing 0.5 to 5.0% C20:4ˆ6 (wt:wt) increased within 8 days, in a dose-dependent manner the C20:4ˆ6 content of jejunal and ileal mucosa phospholipids, with a reciprocal decrease of C18:2ˆ6.…”
Section: Discussionmentioning
confidence: 99%